The Effect of Learning Models and Rational Thinking Abilities on the Outcomes of Students Learning Science Class V State Elementary Schools in Percut Sei Tuan District - Dyan Loka Vitha Wacy; Abdul Muin Sibuea; R. Mursid (BIRCU, 2020)
This study aims to increase students' historical awareness by using the Project-Based Learning (PjBL) model based on the outdoor study of Sukuh temple in social studies learning in class VII SMPIT MTA Karanganyar. This research is a Classroom Action Research (CAR) with a design of two cycles of the application of the learning model in class VII students, totaling 32 students. Data collection was carried out through in-depth interviews, observation, and document analysis. The research instrument is the author himself as a data collector. The data validation was done by using triangulation techniques, double-checking, and peer question and answer. Data analysis was performed using interactive analysis techniques which included data collection, data reduction, data display, and verification of conclusion. To increase students' historical awareness, the researcher used a 30 item historical awareness questionnaire with the achievement of the results of an increase in pre-action and post-action activities. This increase can be seen from the average result value of cycle 1 and cycle 2. The results show that the Project Based Learning (PjBL) model based on the outdoor study of Sukuh temple can increase the historical awareness of grade VII students of SMPIT MTA Karanganyar. The results of the application of the PjBL model have an average post-test score of 66 while the post test score in cycle 2 is 73. The increase in historical awareness of students in cycle 1 and cycle 2 has a percentage of 11% while the comparison between pre-action and cycle 1 has a percentage of 69% so that it can It was concluded that there had been a significant increase in the results of the posttest. Thus, the PjBL model succeeded in increasing the historical awareness of the seventh-grade students of SMPIT MTA Karanganyar.